Personal Factors on The Behavior of Interactionist Traders in a Traditional Market Environment and Semi Modern (Ethnographic Study on the market in Malang Regency) - Saudah, Saudah (Proceedings of International Conference of Graduate School on Sustainability, 2017)
This dissertation research that has been done, obtained financial support from the Ministry of DP3M Ministry of Technology Research and Higher Education of the Republic of Indonesia in year 2017. The results of this interactionist behavior of traders research, was to respond to the insufficiency of structured studies of market status changes from traditional status toward semi-modern. The reality of increasing status of the perpetually growing market is solely determined by the physical facilities and the quantity number of the commodity. This view has been deteriorated by market participants themselves, because in fact it is not just a commodity transaction markets with all the facilities, but positioning market institutions that offer new norms. Put in depth about the market culture, the more it is revealed the important role of the traders lead as the actor that drives the changes in the social structure of the market. Even the trader’s personal factors are contributing in shaping new identity with its own characteristics. Using ethnographic studies as well as the participatory approach of the semi-participative survey, then during the process of the research it is easy to expose the data of 16 informants, and systematically follow the movement in four (4) of the trade network of the vegetables. The snowball technique surely supports the application of qualitative interactive analysis, so that the verification of the analysis results can be directly discussed. Results of the study can be described as follows: (1) personal factors that encourage the growth of the trade’s interactionist behavior which is dominated by the closeness, openness, and commitment; (2) the concept of self-traders represent its position as regulator of the commodity chain supply; (3) the presentation of self-traders reflected on the assertive style in building relationships with other merchants; (4) the communication behavior using symbols of the cultural context of the low and the high context on constant basis; (5) the communication pattern occurs in a similar structured conventional on commodities traders; and (6) mobile media is used to interact with the other traders outside the market.